IDENTIFIKASI TANAMAN PAKAN DAN PERILAKU LEBAH (Trigona sp.) DI DAERAH PENYANGGA KAWASAN TAMAN NASIONAL BOGANI NANI WARTABONE - Zakaria, Zuliyanto; Ibrahim, Nurain; Febriyanti; Ahmad, Jusna; Pratama Solihin , Angry; Tri Nugroho, Bagus (Jurnal Biogenerasi, 2024)
The purpose of this study is to identify the kind of feed plant and Trigona sp. behavior in the buffer area of Bogani Nani Wartabone National Park. It is a quantitative descriptive method. Bee trips to feed trees were directly observed in order to identify the feed plants, and the results were confirmed through examination of the morphology of the pollen. Acetolysis is a technology used in the pollen extraction process. The study's findings identified six different plant species that provide food for Trigona sp. bees: Zinnia peruviana, Mangifera indica, Arachis hypogaea, Turnera subulata, and Antingonon leptopus. According to the results of the pollen identification process, eight plant species Antingonon leptopus, Cocos nucifera, Turnera ulmifolia, Turnera subulata, Chamaecrista calycioides, Arachis hypogaea, and Sida rhombifolia contributed as a source of feed. A. leptopus and C. nucifera are the two plants that receive the most visits, and 08.00–12.00 is the busiest hour.